2015
DOI: 10.1109/tsp.2014.2388436
|View full text |Cite
|
Sign up to set email alerts
|

Robust Multiple Signal Classification via Probability Measure Transformation

Abstract: In this paper, we introduce a new framework for robust multiple signal classification (MUSIC). The proposed framework, called robust measure-transformed (MT) MUSIC, is based on applying a transform to the probability distribution of the received signals, i.e., transformation of the probability measure defined on the observation space. In robust MT-MUSIC, the sample covariance is replaced by the empirical MT-covariance. By judicious choice of the transform we show that: (1) the resulting empirical MT-covariance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Similarly to the proof of Proposition 3 in [17] it can be shown that if there exists a finite positive constant M ∈ R, such that for all y ∈ C p :…”
Section: Robustness To Outliersmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly to the proof of Proposition 3 in [17] it can be shown that if there exists a finite positive constant M ∈ R, such that for all y ∈ C p :…”
Section: Robustness To Outliersmentioning
confidence: 86%
“…Proof. By (17), (19), the non-singularity of Σ (u) 0 and Σ (u) 1 , inequality (1) in [44], and the triangle inequality:…”
Section: Mt-gqlrtsubmentioning
confidence: 99%
See 1 more Smart Citation
“…The following definition of a transformation on the parametric probability measure P X;θ parallels the transformation on a non-parametric distribution stated as Definition 1 in [29].…”
Section: A Probability Measure Transformmentioning
confidence: 99%
“…Under the proposed gener-alization we show that new estimators can be obtained that can gain sensitivity to higher-order statistical moments, resilience to outliers, and yet have the computational advantages of the first and second-order methods of moments. This generalization, called measure-transformed GQMLE (MT-GQMLE), is based on the probability measure transformation framework that was recently applied to canonical correlation analysis [27], [28], and multiple signal classification [29], [30]. It is worthwhile noting that knowledge of these MT-mean vectors and MT-covariance matrices, which establishes partial information about the underlying distribution, is analogous to the side information in the minimax estimation problem considered in [31].…”
mentioning
confidence: 99%